Design of a Creative Economy Actor Learning Community Model for the Empowerment of Former Indonesian Migrant Workers - Yusmanto Yusmanto; Uyu Wahyudi; Ace Suryadi; Asep Saepudin; Froilan Delute Mobo (Journal of Nonformal Education, 2024)
Attention to migrant workers is a cross-sectoral joint work, such as the penta-helix approach, especially when they change status to former migrant workers. The community can empower former migrant workers by paying attention to their potential. The purpose of the research is to provide ideas for the design of learning community models for creative economy actors in the performing arts sub-sector for former migrant workers. The research methodology approaches quantitatively two creative economy communities. The research sample of former migrant workers who are members of the creative economy community engaged in the performing arts sub-sector was 65 people. Research findings that the empowerment of former Indonesian migrant workers can be done with a non-formal learning approach. Through an andragogy approach, learning organizations, adult habits, and non-formal learning components encourage the entrepreneurial independence of creative economy actors, thus providing a reference for a learning community model design with six stages (community negotiation, activity planning, Training on the job, strengthening social networks, performance actions, activity evaluation). The conclusion of the research results shows the impact of the development of former migrant workers, after participating in activities in the creative economy community can exploit themselves and stimulate the embryo of a business group that is integrated between non-formal learning and a facility for creative economy activities performing arts.